The development of a web-based internship information sys-tem at DLHK-DIY using the waterfall method - Akbar, Fahmi Malik Namus (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2024)
The Department of Environment and Forestry of the Special Region of Yogyakarta (DLHK-DIY) encounters a significant challenge related to the insufficient integration of information services for the admission of internship and research programs. This has resulted in difficulties for applicants who seek up-to-date information from the offices or departments within DLHK-DIY, as well as challenges in the inefficient management of data by the institution. This research aims to resolve these challenges through the development of a web-based platform designed to optimize the processes of information and data management. As a result, the deployment of this platform will allow applicants to access information with greater ease and efficiency, while simultaneously improving the institution's ability to manage applicant data. The development methodology for this platform employs the Waterfall approach, encompassing phases such as Needs Analysis, System Design, Implementation, and Testing. The results of this study are projected to enhance the efficiency and effectiveness of the internship and research program implementation at DLHK-DIY. The progress of information technology in the realm of public services, as exemplified by this initiative, is expected to significantly influence service enhancement and data management within the institution.